Agglomeration and the effect of process conditions on fluidized bed combustion of biomasses with olivine and silica sand as bed materials: Pilot-scale investigation. (November 2020) - Morris, Jonathan D.; Daood, Syed Sheraz; Nimmo, William
Abstract: Bubbling fluidized bed combustion of biomass has benefits of fuel flexibility, high combustion efficiency, and lower emissions. Bed agglomeration is where bed particles adhere together with alkali silicate melts and can lead to unscheduled plant shutdown. This pilot-scale study investigates performance and agglomeration when varying fuel (white wood, oat hull waste, miscanthus, wheat straw), bed height, bed material, and includes a novel spatial analysis of agglomerates from different bed locations. White wood was the best performing fuel and did not undergo bed defluidization due to its low ash content (0.5% mass as received), whereas wheat straw (6.67% mass as received ash) performed worst (defluidization times <25 min). Olivine was a superior bed material to silica sand, with 25%+ longer defluidization times with the worst performing fuel (wheat straw). Calcium-rich layers formed at olivine particle surfaces within wheat straw ash melts, and capillary action drew potassium silicate melt fractions into olivine particle fractures. An analysis of agglomerate samples from different bed spatial locations following tests with oat hull waste showed that ash layers on agglomerates retrieved further from the landing point of fuel onto the bed had reduced potassium and elevated calcium, likely due to reduced availability of fresh fuel ash for reaction with bed material. Graphical abstract: Image 1 Highlights: Pilot-scale operation and agglomeration study of biomass in fluidized bed combustor. Agglomeration mechanisms compared between alternative bed materials and silica sand. Lower fuel ash and alkali metal contents increase defluidization time. Olivine bed material increase defluidization time by 25%+ vs. silica sand. Agglomerates sampled from upper, central bed zones had more potassium, less calcium.